A Comparative Analysis of Male and Female Students’ Academic Performance Using Andragogical Approach: A Case Study of National Open University of Nigeria - Fagbemi, Ayodele O. (West African Journal of Open and Flexible Learning, 2016)
This study compared the academic performance of male and female students studying for a Postgraduate Diploma in Distance Education programme at the National Open University of Nigeria, taught through the andragogical approach. The study is part of a larger study on students’ readiness to learn. The academic performance of students in the Measurement and Evaluation course was analysed. The survey research design was adopted. A 32 – item questionnaire was designed to gather information on the variables of the study from the respondents. The Cronbach’s alpha for the measures is .84. The Spearman brown coefficient is .91 while the Guttmann Split half correlation is .91. A convenience sample of 120 students out of the 169 students that sat for the Measurement and Evaluation examination at the NOUN headquarters in Lagos was used. The random sampling table was used to select the respondents. Collected data were analysed by computing frequencies and percentages. There is no significant difference in the scores of male and female students in the Measurement and Evaluation.